2009
DOI: 10.2165/11311000-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment Disorder

Abstract: Adjustment disorder (AD) was introduced into the psychiatric classification systems almost thirty years ago although the concept was recognised for many years before that. Six subtypes are described based on the predominant symptoms but no further diagnostic criteria are offered to assist the clinician. These are common conditions especially in primary care and in consultation liaison psychiatry where the prevalence ranges from 11-18% and 10-35% respectively. Yet they are under-researched, possibly due to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(15 citation statements)
references
References 60 publications
(46 reference statements)
1
14
0
Order By: Relevance
“…The results of the screening study demonstrated the prevalence of a decrease in stress resistance and subjective deterioration in all age groups with an increase to 50.9% in the age group 51-65 years. The data obtained are comparable with international studies [3], [7], [8], [22], [23]. These studies emphasize the importance of assessing the condition of patients with the AD and choosing the safest therapy.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The results of the screening study demonstrated the prevalence of a decrease in stress resistance and subjective deterioration in all age groups with an increase to 50.9% in the age group 51-65 years. The data obtained are comparable with international studies [3], [7], [8], [22], [23]. These studies emphasize the importance of assessing the condition of patients with the AD and choosing the safest therapy.…”
Section: Resultssupporting
confidence: 83%
“…The persistent or chronic AD can last more than 6 months, especially if the stressor continues, for example, in case of unemployment. Many publications note that AD is most often (up to 37%) observed in primary health care facilities and outpatient psychiatric practice [7], [8]. The AD has high co-morbidity with depression, anxiety, mixed anxiety-depressive states, behavioral disorders, substance abuse.…”
Section: Signi Icant Deterioration In Social Professional or Other Imentioning
confidence: 99%
“…Personal circumstances and context of the stressor, relation between symptom severity and stressor, persistence beyond the expected time period, cultural norms for emotional response/expression and duration and severity of dysfunction can be useful guide to make a diagnosis of adjustment disorder. [3] Major depression should be considered as the diagnosis when symptoms meet the diagnostic threshold of depression. Exacerbation of maladjustment in personality disorders when faced with severe stress can result in symptoms of adjustment disorder.…”
Section: Current Nosological Statusmentioning
confidence: 99%
“…The other option of DSM-IV for emphasizing the role of stress in the clinical status of the patient lies in the use of specific diagnostic rubrics (acute stress disorder, posttraumatic stress disorder) or broad diagnoses (adjustment disorders). However, the category of adjustment disorders has displayed major conceptual and methodological flaws [6,7,8]. A major problem is the fact that it is an exclusion diagnosis (it cannot be applied in comorbidity with other psychiatric disorders) and overlaps with subthreshold manifestations of mood and anxiety disorders [9,10,11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%